Prevalence of four urogenital sexually transmitted infections in a dedicated clinic from Lisbon - Zohra Lodhia; Jacinta Azevedo; João Alves; Dora Cordeiro; Marília Antunes; Maria J. Borrego (Sociedade Portuguesa de Dermatologia e Venereologia, 2023)
Background/Objectives: To determine the prevalence of urogenital chlamydia trachomatis (CT), neisseria gonorrhoeae (NG), trichomonas vaginalis (TV), and mycoplasma genitalium (MG) among attendees of an open and freely available sexually transmitted infections (STI) dedicated clinic in Lisbon, at Centro de Saúde da Lapa, during 1-year. Methods: Molecular testing for CT, NG, MG, and TV was performed on 1,062 urogenital specimens (one specimen per person). A descriptive, crosssectional, observational study was conducted to evaluate the characteristics of infected persons. Statistical analysis was performed. Results: Around 237 infections were detected in 214 patients. CT was the most prevalent (11.6%), with a similar infection rate between men and women. NG was the second most frequently detected (7.3%), followed by MG and TV (2.9 and 0.5%, respectively). Statistically significant associations were found: 1) between younger age and CT and NG prevalence, where being < 25 years old constituted an increased risk factor; 2) between CT and NG prevalence and sexual orientation, where heterosexuals presented an increased risk for CT infections while men who have sex with men (MSM) had a higher risk for NG infections; and 3) between "having symptoms" and gonococcal infection. Conclusions: This study highlights the rising of CT and NG in contrast to a low rate of MG and to the scarceness of TV.